Rhizosphere engineering for semiarid tropics: prospects and bottlenecks - Anurag Yadav; Kusum Yadav; Rumana Ahmad (Academia Biology)
Rhizosphere engineering is a cutting-edge biotechnological approach, strategically employing microbial biofertilizers, phytostimulants, and plant growth promoting rhizobacteria (PGPR) to boost agricultural crop productivity. Unlike conventional chemical fertilizers, this method eliminates harmful substances, mitigating environmental and health concerns. The foundation of rhizosphere engineering lies in the intricate study of plant–microbe interactions, where soil microorganisms play a pivotal role in nutrient cycling, agricultural waste decomposition, and plant growth stimulation. Rhizosphere engineering shows immense promise in the semiarid tropics, covering around 26% of the Earth's ecology and characterized by water scarcity and high temperatures. Microorganisms found in the rhizosphere, endosphere, and vegetation of arid plants have adapted to harsh environmental conditions, offering valuable resources for biofertilizer and biocontrol research. Their application in enhancing water and nutrient absorption can help alleviate water stress, contributing to sustainable crop production in these regions. However, fully realizing the potential of rhizosphere engineering presents numerous challenges. Identifying beneficial microorganisms, establishing standardized protocols, comprehending complex plant–microbe–soil interactions, and developing efficient delivery systems for microbial inoculants are among the bottlenecks that must be addressed. These challenges underscore the need for continuous research and innovation in this field. Despite being in its infancy, rhizosphere engineering has already accumulated a wealth of information and insights. By surmounting existing challenges and harnessing the power of PGPR and other rhizosphere microorganisms, rhizosphere engineering may usher in a new era in agriculture, particularly benefiting the water-stressed regions of the semiarid tropics.